2008
DOI: 10.1248/cpb.56.1073
|View full text |Cite
|
Sign up to set email alerts
|

Formulation Study of Intravesical Oxybutynin Instillation Solution with Enhanced Retention in Bladder

Abstract: A formulation study of intravesical oxybutynin (OB) preparations was carried out in order to improve the effectiveness in intravesical instillation therapy for spastic neurogenetic bladder. Sodium hyaluronate (HYA) was introduced to enhance the muco-adhesiveness of the instillation preparation, and the physicochemical properties of the OB formulation were evaluated in comparison with a conventional formulation containing hydroxypropylcellulose (HPC). The viscous properties and in vitro adhesiveness increased w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…19 Recently; in the urological field, the application of a large variety of bioadhesive polymers such as chitosan, polycarbophil, and hydroxypropylcellulose (HPC) has been reported. 38 For instance, Chiba et al 39 demonstrated that the addition of 1.0% HPC effectively prolonged oxybutynin retention in the bladder compared to intravesical instillation of its solution. Among these bioadhesives, chitosan is a featured natural copolymer exhibiting various beneficial properties such as strong bioadhesion, controlled drug-releasing properties, and permeation-enhancing properties due to its cationic character and based on its primary amino groups.…”
Section: Preparation Of Chitosan and Plx Gelsmentioning
confidence: 99%
“…19 Recently; in the urological field, the application of a large variety of bioadhesive polymers such as chitosan, polycarbophil, and hydroxypropylcellulose (HPC) has been reported. 38 For instance, Chiba et al 39 demonstrated that the addition of 1.0% HPC effectively prolonged oxybutynin retention in the bladder compared to intravesical instillation of its solution. Among these bioadhesives, chitosan is a featured natural copolymer exhibiting various beneficial properties such as strong bioadhesion, controlled drug-releasing properties, and permeation-enhancing properties due to its cationic character and based on its primary amino groups.…”
Section: Preparation Of Chitosan and Plx Gelsmentioning
confidence: 99%
“…For irrigations for the bladder iso-osmosis is less important. Hypo-osmosis is more problematic than hyper-osmosis, because the osmotic value of urine is twice to thrice the osmotic value of blood [4].…”
Section: Osmotic Valuementioning
confidence: 99%
“…Irrigations for rinsing normally should not be viscous. In solutions for intravesical use the use of a viscosity enhancer, like hypromellose, may exert a prolonged effect [4].…”
Section: Viscositymentioning
confidence: 99%